Pengembangan Sistem Informasi Manajemen Persuratan di Badan Informasi Geospasial - Kurniawati, Kurniawati (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2021)
A business organization certainly really needs an information system as an application of information technology in bridging the problems that occur, information systems have several types including Management, Accounting, Finance, Manufacturing, Human Resources, Marketing, and Executive information systems. CV APJ Meat Shop Bogor until now does not have a sufficiently qualified promotional media, with plans to build a web-based company profile, hopefully it can make this company better known and make it easier for the public to find information about this company. The purpose of this research is to provide information to the wider community about APJ MEAT SHOP and make it easier for APJ MEAT SHOP in introducing the products being sold. The research method used is Waterfall. What can be taken from the creation of the Company Profile Website on the CV APJ MEAT SHOP are as follows: (i) The website is designed to run well according to the desired needs. (ii) The Company Profile Website is made based on the business processes that occur in the company.